2021
DOI: 10.3390/jor1010007
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire Smoke Exposure: Covid19 Comorbidity?

Abstract: Air pollution, particularly fine and ultrafine particulate matter aerosols, underlies a wide range of communicable and non-communicable disease affecting many systems including the cardiopulmonary and immune systems, and arises primarily from transportation and industry. A number of air pollution driven diseases also are Covid19 comorbidities. Thus, a number of studies on air pollution exposure, particularly particulate matter, strongly indicate air pollution is an important underlying factor in Covid19 transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…The first is that particulate matter might carry the airborne virus, transmitting it into the human respiratory system ( Copat et al, 2020 ; Martelletti and Martelletti, 2020 ; Di Girolamo, 2021 ; Nor et al, 2021 ). The second is that fine particulate matter could increase the severity of the Covid-19 disease by delaying or complicating recovering ( Domingo and Rovira, 2020 ; Leifer et al, 2021 ). However, it is difficult to distinguish between these two mechanisms, due to a lack of individual-related longitudinal data that are not available in the midst of a pandemic ( Villeneuve and Goldberg, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first is that particulate matter might carry the airborne virus, transmitting it into the human respiratory system ( Copat et al, 2020 ; Martelletti and Martelletti, 2020 ; Di Girolamo, 2021 ; Nor et al, 2021 ). The second is that fine particulate matter could increase the severity of the Covid-19 disease by delaying or complicating recovering ( Domingo and Rovira, 2020 ; Leifer et al, 2021 ). However, it is difficult to distinguish between these two mechanisms, due to a lack of individual-related longitudinal data that are not available in the midst of a pandemic ( Villeneuve and Goldberg, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Leifer et al observed increased numbers of COVID-19 cases following wildfire smoke events in Orange County, California (ref. [ 31 ]). However, our study significantly improved on these studies by controlling for additional covariates: the general prevalence of the virus, which increased over time (not included in Meo et al); and temperature and the number of tests administered (not included in Meo et al or Leifer et al).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Laudares and Gagliardi (2020) analyzed the potential of deforestation and spread of COVID-19 affecting indigenous people and found that deforestation of 1 km 2 area resulted in 9.5% new COVID-19 cases. Association between wildfire incidences with COVID-19 cases and severity has been reported even though the number of these correlation studies were observed to be less compared to wider literature on ambient air pollution and COVID-19 ( Meo et al, 2020 ; Firebaugh et al, 2021 ; Kiser et al, 2021 ; Leifer et al, 2021 ; Zhou et al, 2021 a). Of this, Meo et al (2020) found that wildfire allied pollutants, particulate matter PM 2.5 and CO is associated positively with COVID-19 daily cases and cumulative deaths.…”
Section: Deforestationmentioning
confidence: 99%
“…Secondary transmission routes are also plausible. For example, air quality can be reduced due to higher levels of pollutants from wildfires and other activities, which have shown to lead to strong impacts upon contracting COVID-19 ( Liu et al, 2020a ; Meo et al, 2020 ; Middleton, 2020 ; Curtis, 2021 ; Dragone et al, 2021 ; Kiser et al, 2021 ; Leifer et al, 2021 ; Setti et al, 2020 b; Zhou et al, 2021 a). Furthermore, natural ventilation for optimal indoor air quality is not sufficient to control the potential spread of SARS-CoV-2 ( Li et al, 2004 ; Meiss et al, 2021a ; WHO, 2021a).…”
Section: Impact Of Ambient Environments On Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation